Advanced Therapy Medicinal Products for Eye Diseases: Goals and Challenges - Yolanda Diebold (MDPI AG, 2021)
Advanced therapy medicinal products (ATMPs) are a novel class of medicines with enormous potential to improve treatments for a wide range of diseases, including those affecting eye structures [...]